Anteseden pemanfaatan insentif PPh final UMKM di masa pandemi - Usman Nur Hamzah (Keberlanjutan)
The utilization of tax incentives, especially the incentive of final income tax of MSMEs (micro, small, and medium enterprises), is still considered low from the predetermined allocation. This study aims to analyze the factors that influence the utilization of MSMEs' final income tax incentives during the covid-19 pandemic. This research was conducted by distributing questionnaires to Msmes taxpayers in the working area of KPP Pratama Probolinggo. The data analysis method uses structural equation modeling (SEM) with 147 respondents as the research sample. The results showed that taxpayers' knowledge about the MSMEs' final income tax incentives significantly affected the intention to apply the incentives. Besides that, the socialization of the MSMEs' final income tax incentives significantly affects the intention to apply the incentives through knowledge. Perceived value and financial condition do not significantly affect the intention to apply the incentives. Educational socialization about MSMEs' final income tax incentives must be carried out effectively so taxpayer knowledge can further increase the intention to take advantage of MSMEs' final tax incentives.